High-Yield Gas-Phase Laser Photolysis Synthesis of Germanium Nanocrystals for High-Performance Photodetectors and Lithium Ion Batteries - Kim, Chang Hyun; Im, Hyung Soon; Cho, Yong Jae; Jung, Chan Su; Jang, Dong Myung; Myung, Yoon; Kim, Han Sung; Back, Seung Hyuk; Lim, Young Rok; Lee, Chi-Woo; Park, Jeunghee; Song, Min Seob; et al. (American Chemical Society, 2012)
We developed a new high-yield synthesis method of free-standing germanium nanocrystals (Ge NCs) by means of the gas-phase photolysis of tetramethyl germanium in a closed reactor using a Nd:YAG pulsed laser. The as-grown Ge NCs are sheathed with thin (1-2 nm) carbon layers, and size control (5-100 nm) can be simply achieved using a quenching gas. The hybrid nanostructures of the quantum-confined Ge NCs and reduced graphene oxide (RGO) become transparent flexible photodetectors that respond sensitively over the UV-visible-NIR wavelength range. Both Ge NCs and Ge-RGO hybrids exhibit excellent cycling performance and high capacity of the lithium ion battery (800 and 1100 mA h/g after 50 cycles, respectively) as promising anode materials for the development of high-performance lithium batteries.